Digital Analysis of Myocardial Contrast Echocardiography: A Clinical Study Using an Air-Filled Agent in Normal Subjects - GEISER, EDWARD A.; MILBURN, DEANNA J.; CUNNINGHAM, MICHAEL S.; BROWN, CHRISTOPHER S.; LIN, LANG; WILSON, DAVID C. (Echocardiography (Mount Kisco, N.Y.), 2000)
The purpose of the present study was to determine whether direct digital image analysis would allow improved detection of myocardial contrast. Eighteen normal subjects were recruited and separated into two groups. In group 1, the time‐brightness curves of the left ventricular cavity and three myocardial perfusion beds were formed from digitized video tape, with output power and imaging time as secondary variables. In group 2, curves constructed from direct polar digital data were compared, with fundamental and second harmonic image formation as variables. In group 1 subjects, using fundamental imaging, the area under the curve in the left ventricular cavity increased slightly with intermittent imaging. No consistent myocardial opacification was identified. In group 2 subjects, using intermittent imaging, the area under the myocardial curve and peak intensity increased with high output second harmonic imaging in the left anterior descending and right coronary artery regions. Intermittent, second harmonic imaging and digital processing can demonstrate myocardial contrast even with an air‐filled agent.